Nilai-Nilai Pembangun Karakter: Permainan Tradisional Karetan/Pelencatan Suku Using di Banyuwangi - Roudhotul Jannah; Arya Mahdi; Harjianto Harjianto (Universitas Batanghari Jambi, 2019)
The traditional game of karetan / pelencatan is the term of traditional game for Using tribe in Banyuwangi Regency. The traditional game of karetan / pelencatan uses a simple materials or tools from woven rubber bands (rubber bands strands). According to the size of agreement, usually about 3 or 4 meters in length, which is played in an open space and quite wide. The method used in this research is the ethnographic qualitative. This research examines the values of character building in traditional game of karetan / pelencatan in the community of Kemiren and Kabat village, whose the majority population is Using tribe. Data collection techniques used is observation, interview, and documentation. The result of the research on children's traditional games of karetan / pelencatan not only as a playing facility, but also as a medium to shape the children's character, such as; belief in the power of the One Almighty God, honesty in the game, hard work in achieving victory, national spirit, and interaction with the social environment.